Comparative study on immunomodulatory and growth enhancing effects of three prebiotics (galactooligosaccharide, fructooligosaccharide and inulin) in common carp (Cyprinus carpio). (11th August 2016) - Hoseinifar, Seyed Hossein; Ahmadi, Alireza; Raeisi, Mojtaba; Hoseini, Seyyed Morteza; Khalili, Mohsen; Behnampour, Nasser
Abstract: This study investigated the effects of different prebiotics, including galactooligosaccharide (GOS), fructooligosaccharide (FOS) and inulin (INL), on skin mucosal immune parameters, humoral immune responses as well as performance of common carp ( Cyprinus carpio ). Two hundred and forty specimens (13.85 ± 0.85 g) were stocked in 12 fibreglass tanks assigned into three treatments and a control group. The experimental diets were formulated to have equal level (2%) of the prebiotics. At the end of the feeding trial, the highest skin mucus lysozyme activities and total immunoglobulin (total Ig) were observed in GOS‐fed group ( P  <   0.05). However, skin mucus protease activity showed no significant difference among different dietary groups ( P  <   0.05). Blood respiratory burst activity was significantly increased in all prebiotic‐fed fish compared to the control group ( P  <   0.05); the highest activity was observed in GOS treatment. Furthermore, evaluation of humoral immune response revealed that feeding with GOS‐supplemented diet significantly increased lysozyme and alternative complement (ACH50) activity as well as total Ig compared to the control and other prebiotic groups. While no significant difference was observed between FOS and INL groups, common carps fed GOS‐supplemented displayed improved ( P  <   0.05) growth performance, including final weight, weight gain, specific growth rate (SGR) and feed conversion ratio (FCR), compared to the control treatment. These results revealed that different prebiotics modulate carp growth and immune response in different manner, and GOS seems to be the most suitable prebiotic.